National security strategic tasks of the Republic of Poland at the turn of the second and third decade of the twenty-first century (Economic and Political Thought, 2016)
This article presents the main strategic tasks that Poland should take tostrengthen their own security in the next 5 to 10 years. The first and particularlyimportant task is to continue the cycle of national strategic planning. It isnecessary to complete the development of basic directive and planning documentsto ensure the implementation of the adopted in 2014, the new NationalSecurity Strategy, and at the same time to start another Strategic Review ofNational Security, starting a new cycle of planning. Six tasks concern the practical,organisational and technical strengthening Poland’s own security capabilities.These include: the consolidation of the system of national securitymanagement, building a system of strategic resilience to aggression, organizingnational information security system, including the acceleration of theconstruction of the cyber security system, improving preparation of reservemobilisation and reform of the National Reserve Forces, implementationof the ‘third wave’ of technical modernisation of the Polish Armed Forces– cyber-defence, unmanned systems, precision-guided weapons, launch andimplementation of the National Programme for unmanned systems (flywheelof innovation for security and development). The third part of the tasks refersto activities aimed at strengthening the Poland’s external security pillars.These are measures to strengthen the North Atlantic Treaty Organisation,the strategic actions leading to the empowerment of the European Union andthe development of cooperation between NATO and the EU (political andstrategic response to hybrid threats) and strengthening strategic partnerships,especially the alliance with the US.